2013
DOI: 10.1590/s1980-57642013dn74000004
|View full text |Cite
|
Sign up to set email alerts
|

Mattis Dementia Rating Scale (DRS): Normative data for the Brazilian middle-age and elderly populations

Abstract: OBJECTIVETo expand norms for the Mattis Dementia Rating Scale (DRS) for the Brazilian middle-age and elderly populations.METHODSThe DRS was administered to 502 individuals without cognitive deficits, 312 women and 190 men, aged 50 years or over and with educational level ranging from 0 to 13 years or more. The sample was composed of subjects who participated in other studies, from Caeté (Minas Gerais state), Ribeirão Preto (São Paulo state) and São Paulo (São Paulo state). Participants were divided into four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
(17 reference statements)
0
30
0
7
Order By: Relevance
“…This cognitive tool was also administered in the illiterate population in Brazil. These results showed that illiterate people performed significantly lower than their literate counterparts [22].…”
Section: Discussionmentioning
confidence: 87%
“…This cognitive tool was also administered in the illiterate population in Brazil. These results showed that illiterate people performed significantly lower than their literate counterparts [22].…”
Section: Discussionmentioning
confidence: 87%
“…A EMAD originalmente foi desenvolvida para avaliar o status cognitivo de indivíduos com disfunção cerebral, aqueles com comprometimento cognitivo, principalmente de tipo degenerativo (Porto et al, 2003) e diagnóstico de DA. No entanto, é muito utilizada para a detecção precoce de demência e diagnóstico diferencial entre DA e outros tipos de demência (Foss et al, 2013). Ela compreende 5 subescalas: Atenção, Iniciação/Perseveração, Construção, Conceituação e Memória (Porto et al, 2003;Lavoie et al, 2015).…”
Section: Memória De Figuras (Tmf) Tfv (Categoria Animais) Teste Do unclassified
“…Foram analisadas a frequência e percentual de comprometimento das variáveis baseado no desempenho abaixo do ponto de corte para demência na BBRC (Radanovic, et al, 2007;Charchat-Fichman et al, 2013) e valor de Z abaixo de -2 na EMAD (Foss et al, 2013), respectivamente, na tabela 6 e 7 abaixo: …”
Section: Percentual De Comprometimento Das Variáveis Cognitivasunclassified
See 2 more Smart Citations